ANALISIS KETERSEDIAAN AIR DAN KEANDALAN KULONG PL KECAMATAN PANGKALAN BARU MENGGUNAKAN MODEL SARIMA DAN SOR - Sisillia Jesika Pririzki; Adriyansyah Adriyansyah; Hendy Stevanus; Rohil Agatha Lusia (Jurusan Teknik Sipil Universitas Bangka Belitung, 2022)
Air Mesu Village and Jeruk Village are two villages located in Pangkalan Baru District, Central Bangka Regency, Bangka Belitung Islands Province. The number of residents in the village increases every year, so that causes problem, the problem is needs of clean water will be increas. The solution to this problem is to use Kulong PL water as a source of raw water to meet the needs of clean water in Air Mesu Village and Jeruk Village. To ensure the availability of Kulong PL water is able to meet the needs of clean water in Air Mesu Village and Jeruk Village, a prediction will be made for the next 10 years, starting from 2021 to 2030. From the analysis results, the best model for predicting is SARIMA (0 ,0,0)(1,1,0)12 . Based on the SOR analysis, the best option in using Kulong PL is to focus on one village only. If the use of Kulong PL likes 100% then the permitted use is 3,06 l/det. As for Jeruk Village, Kulong PL is able to supply 100% of the needs with a 99% weight level.